Exploring organizational digital readiness to offer youth E-Mentoring - Kaufman, Michelle R.; Zhou, Xiaobin; Yenokyan, Gayane; Levine, Deborah K.; Wright, Kate; Salcido, Maritza; Garringer, Michael; Palen, Lori Ann (Mentoring & Tutoring, 2024)
The COVID-19 pandemic prompted many youth mentoring programs to offer digital services (e-mentoring). The sustained success of these efforts depended, in large part, on organizations’ digital readiness. Although there are established, broad measures of digital readiness, mentoring organizations have unique requirements for readiness that have not been previously measured. The current cross-sectional survey research study measured the state of digital readiness for youth mentoring organizations and tested the organizational E-Mentoring Readiness Scale. Ninety-five representatives from U.S. mentoring programs completed an online survey. Participants felt mentors, mentees, and families were moderately comfortable with e-mentoring. There was less confidence and comfort with the required technology and execution of e-mentoring. A confirmatory factor analysis of the E-Mentoring Readiness Scale showed two distinct but related factors with good model fit. An honest assessment using this tool may allow the youth mentoring field to move into the digital age more seamlessly.
CRIS-Team Scopus Importer:2024-05-24
Keywords: digital mentoring; digital readiness; e-mentoring; Mentoring; technology; youth development